Análise da dureza e resistência de união de resinas Bulk Fill em restaurações de cavidades classe II expostas à luz LED de um fotopolimerizador de baixo custo - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Budget light-curing units (LCU) presenting fiber guides with small diameter and non-homogeneous light beam profile are widely available in the Dental market. However, to date, there is no information in the literature regarding the effectiveness of such LCUs on microhardness of bulk fill resins and on the bond strength of Class II cavity restorations. The aim of this study was to analyze the Vickers microhardness (VHN) and bond strength of low and high viscosity bulk fill resin restorations exposed to light from a budget light curing light. The study, previously approved by the Local Ethics Committee (2,896,938/2018), used 84 third molars (n=7) where standardized Class II (MOD) cavities were made and restored according to the following groups: Tetric N-Ceram Bulk Fill (TNC - Ivoclar Vivadent) single increment; Filtek Bulk Fill Flow (FBF - 3M ESPE, St, Paul, MN, USA) coated with Z250 resin (3M ESPE, St, Paul, MN, USA); and SureFill SDR (SDR - Dentsply Sirona, York, PA, USA) coated with TPH Spectrum resin (Dentsply Sirona). The light attenuation values through restoration in bulk fill composite resin were recorded. The composite resins were light cured with polywave LED (Bluephase 20i - Ivoclar Vivadent) and with budget LED curing light (Rainbow Curing Light - SML). The restored teeth were evaluated in two conditions, 24 h after the restorative procedure and after thermocycling. VHN results were analyzed by 2-way ANOVA with repeated measures followed by Bonferroni's test (α=0.05). The results of bond strength were evaluated by 2-way ANOVA followed by Tukey test (α=0.05). The failure pattern was also analyzed. No comparisons were made between products. For the 24 h condition, only TNC and SDR resins obtained VHN values at the base significantly lower than the top, regardless of the light-curing unit used. The light emitted by the polywave LED promoted higher VHN values than the light emitted by the budget LED. When analyzing the microhardness after thermocycling, the VHN values at the base were significantly lower than those observed at the top regardless of the light curing unit used for SDR and TNC resins. FBF obtained higher hardness values when the polywave LED was used. A significant difference was observed only for the high viscosity resin TNC, with higher values of bond strength for the polywave LED (p = 0.048). When comparing the 24 h and thermocycling intervals, only SDR and FBF resins obtained significantly lower values (p = 0.01 and p = 0.026, respectively. It can be concluded from the study that there is a difference in the microhardness of bulk fill composite resins when cured with polywave LED and budget LED, with higher VHN values for SDR and TNC resins when using the polywave LED. The TNC high viscosity resin obtained superior bond strength values for the polywave LED. Thermocycling interferes with the bond strength in low viscosity bulk fill resins.
Keywords: luz; dureza; resinas compostas; light; hardness; composite resins; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA